Perlindungan Hukum terhadap Karya Cipta Fotografi - I Kadek Candra Wisesa; Desak Gde Dwi Arini; Luh Putu Suryani (Warmadewa Press, 2020)
The richness in the diversity of arts and cultures can be found in the Republic of Indonesia. Intellectual property rights obtain protection as stipulated in legislation, including Law Number 28 of 2014 concerning Copyright. The advancement in technology and the increasingly developing world of digital photography by means of digital cameras raises the legal issues of copyright in photographic works. The main issues examined in this paper are: the forms of legal protection of the rights of the creators of photographic works and the resolution of disputes of photographic works that are used without permission. The method used to examine this issue is the normative legal research method with a legislative approach. Copyright Protection of photographic works may be done in two ways, namely preventive in which legal protection given to the creator of photography which the creator shall done by registering the copyright, and repressive protection realised by filing a lawsuit in court if there is a violation of copyright in the photographic work. All rights reserved must always be appreciated by not committing violating actions which are arbitrarily committed especially if it relates to providing benefits for violators.